The Agency of the Paper Plan: The Building Plans of Late Nineteenth-Century and Early Twentieth-Century Berlin. (March 2020) - Amhoff, Tilo
This article closely investigates the unique visual representations of the building plans of late nineteenth-century and early twentieth-century Berlin, and emphasizes the agency of the paper plan in the profession and discipline of Städtebau . Following positions in German media theory, the paper plan is understood and theorized as a medium of bureaucracy and the plan drawing as a set of cultural techniques. In doing so, the article traces the refinement of the instruments for regulating the building of the city—from the building plan, to the building zones plan, to the town development plan. It is argued that the paper plans themselves have agency in seeing the city and hence thinking about the city (through their methods of visual representation), and agency in the formation of graphic terms and concepts (derived from the making of building plans). The paper plans mediated visual and verbal knowledge of the city that would have been inconceivable without them.